2009
DOI: 10.1038/ejcn.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycaemic index and glycaemic load in the European Prospective Investigation into Cancer and Nutrition

Abstract: Objectives: To describe dietary glycaemic index (GI) and glycaemic load (GL) values in the population participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study according to food groups, nutrients and lifestyle characteristics. Methods: Single 24-h dietary recalls (24-HDRs) from 33 566 subjects were used to calculate dietary GI and GL, and an ad hoc database was created as the main reference source. Mean GI and GL intakes were adjusted for age, total energy intake, height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…Food items containing negligible or no carbohydrates (chiefly meat, fish, fats and eggs) were not assigned any values. Foods that most contributed to the GL estimate were bread (40% among men and 31% among women), fruits (12% and 14%), pasta/rice/ other grains (9% and 8%), sugar and confectionary (7% and 9%), sweet buns/cakes/pies/biscuits (5% and 9%) and vegetables (5% and 5%) [29]. The correlation coefficient between dietary GL and total carbohydrates was 0.91.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Food items containing negligible or no carbohydrates (chiefly meat, fish, fats and eggs) were not assigned any values. Foods that most contributed to the GL estimate were bread (40% among men and 31% among women), fruits (12% and 14%), pasta/rice/ other grains (9% and 8%), sugar and confectionary (7% and 9%), sweet buns/cakes/pies/biscuits (5% and 9%) and vegetables (5% and 5%) [29]. The correlation coefficient between dietary GL and total carbohydrates was 0.91.…”
Section: Methodsmentioning
confidence: 93%
“…GI values of foods were assigned to items reported in the dietary questionnaires in a standardised manner as described in detail elsewhere [29]. In brief, GI values assigned to individual food items were obtained from the FosterPowell table [28], British values [30] and internet updates (www.glycemicindex.com), using glucose as the reference.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no other study has indicated this association. It is important to underscore the effects of white bread on glycaemic changes, acting as a possible obesity cofactor (44) . Foods with a high glycaemic index, like white bread, appear to cause less satiety, more hunger after meals and increase daily energy intake, while foods with a high fibre content have been proposed to be more satiating, reduce hunger and decrease energy intake (45) .…”
Section: Discussionmentioning
confidence: 99%
“…In the Expanded Discussion (see Supplementary Materials), we have tried to define such a threshold by comparing the LC to the Nutrient Density Score (NDS), and have estimated a threshold of 30% above which PBF LC might be relevant. Ideally, human studies would be needed to define such a threshold like those performed for the glycaemic index (GI) whereby foods are clustered within three categories: low GI-foods with a GI below 55, intermediate GI-foods with a GI between 55 and 70 and high-GI foods with a GI above 70 (van Bakel et al, 2009)). Such a classification has important nutritional implications in that it helps guide food choices, e.g.…”
Section: Can Lipotropic Capacity Be a New Tool For Helping To Guide Fmentioning
confidence: 99%